NUMERICAL ANALYSIS AND SCALED-DOWN MODEL OF AIR BARRIER AND BLOCKING ANGLE VARIATIONS IN SUPPLY DUCT DIFFUSER IN HIGH-SPEED TRAIN CABINS TO COMPLY WITH INDONESIAN THERMAL COMFORT - Fauzun, Fauzun; Arif, Mohamad Faizal; Ostaputra, Achmad Kevin; Ilham, Arsyadani Tsalisul; Yogiswara, Cahyo Wibi (Journal of Applied Engineering Science, 2025)
Kereta Cepat Merah Putih (KCMP) was a high-speed train developed by the Indonesian government to enhance intercity travel. A key focus of this development was the HVAC system within the passenger cabin, essential for ensuring passenger comfort. This study investigated the impact of air barrier placement and air flow direction angles (45°, 90°, and 135°) on airspeed and temperature distribution in the cabin. Using CFD simulations with ANSYS Fluent, six variations were tested to determine the optimal configuration. The results identified variation model 3, which employed an air barrier at the top of the ducting system and omitted the use of blocking angles for the air flow direction of the supply diffuser, as the most effective in achieving optimal airspeed and temperature distribution. Following the simulation, experimental measurements were conducted on a scaled-down model of variation 3. Measurements were taken at six sample planes in the supply duct and five in the supply duct diffuser, applying the duct traversing method (ISO 3966) with 25 measurement points per sample plane. The experimental results were then compared with the simulation data to ensure consistency in volumetric flow rate, flow velocity, and air pressure drop parameters. Additionally, comparisons were made with similar trains, measuring air velocity and temperature distribution within their passenger cabins. The findings confirmed that the performance of variation model 3 in the CFD simulation aligned with the scaled-down experimental results, demonstrating consistency in both tests and comparisons.